Role of zoledronic acid in oncolytic virotherapy: Promotion of antitumor effect and prevention of bone destruction. Issue 9 (3rd August 2017) - Yamakawa, Yasuaki; Tazawa, Hiroshi; Hasei, Joe; Osaki, Shuhei; Omori, Toshinori; Sugiu, Kazuhisa; Komatsubara, Tadashi; Uotani, Kouji; Fujiwara, Tomohiro; Yoshida, Aki; Kunisada, Toshiyuki; Urata, Yasuo; et al.
Abstract : Osteosarcoma is an aggressive malignant bone tumor that causes bone destruction. Although tumor‐specific replicating oncolytic adenovirus OBP‐301 induces an antitumor effect in an osteosarcoma tumor, it cannot prevent bone destruction. Zoledronic acid (ZOL) is a clinically available agent that inhibits bone destruction. In this study, we investigated the potential of combination therapy with OBP‐301 and ZOL against osteosarcomas with bone destruction. The antitumor activity of OBP‐301 and ZOL in monotherapy or combination therapy was assessed using three human osteosarcoma cell lines (143B, MNNG/HOS, SaOS‐2). The cytotoxic effect of OBP‐301 and/or ZOL was measured by assay of cell apoptosis. The effect of OBP‐301 and ZOL on osteoclast activation was investigated. The potential of combination therapy against tumor growth and bone destruction was analyzed using an orthotopic 143B osteosarcoma xenograft tumor model. OBP‐301 and ZOL decreased the viability of human osteosarcoma cells. Combination therapy with OBP‐301 and ZOL displayed a synergistic antitumor effect, in which OBP‐301 promoted apoptosis through suppression of anti‐apoptotic myeloid cell leukemia 1 (MCL1). Combination therapy significantly inhibited tumor‐mediated osteoclast activation, tumor growth and bone destruction compared to monotherapy. These results suggest that combination therapy of OBP‐301 and ZOL suppresses osteosarcoma progression via suppression of MCL1 and osteoclast activation. Abstract : Combination therapy with oncolytic adenovirus OBP‐301 and zoledronic acid displayed a synergistic antitumor effect against osteosarcoma cells. Combination therapy inhibited in vivo tumor growth and bone destruction against bone‐invasive osteosarcoma.